Clinical experience of noninvasive prenatal testing for rare chromosome abnormalities in singleton pregnancies - Hu, Ting; Wang, Jiamin; Zhu, Qian; Zhang, Zhu; Hu, Rui; Xiao, Like; Yang, Yunyuan; Liao, Na; Liu, Sha; Wang, He; Niu, Xiaoyu; Liu, Shanling (Frontiers in Genetics, 2022)
ABSTRACT Objectives: To investigate the clinical use of noninvasive prenatal testing (NIPT) for common fetal aneuploidies as a prenatal screening tool for the detection of rare chromosomal abnormalities (RCAs). Methods: Gravidas with positive NIPT results for RCAs who subsequently underwent amniocentesis for a single nucleotide polymorphism array (SNP array) were recruited. The degrees of concordance between the NIPT and SNP array were classified into full concordance, partial concordance, and discordance. The positive predictive value (PPV) was used to evaluate the performance of NIPT. Results: The screen positivity rate of NIPT for RCAs was 0.5% (842/158,824). Of the 528 gravidas who underwent amniocentesis, 29.2% (154/528) were confirmed to have positive prenatal SNP array results. PPVs for rare autosomal trisomies (RATs) and segmental imbalances were 6.1% (7/115) and 21.1% (87/413), respectively. Regions of homozygosity/uniparental disomy (ROH/UPD) were identified in 9.5% (50/528) of gravidas. The PPV for clinically significant findings was 8.0% (42/528), including seven cases with mosaic RATs, 30 with pathogenic/likely pathogenic copy number variants, and five with imprinting disorders. Conclusions: NIPT for common fetal aneuploidies yielded low PPV for RATs, moderate PPV for segmental imbalances, and incidental findings for ROH/UPD. Due to the low PPV for clinically significant findings, NIPT for common fetal aneuploidies need to be noticed for RCAs.